The Method of Goalkeeper's Evaluation in Futsal - Szwarc Andrzej; Oszmaniec Mateusz; Lipinska Patrycja (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2014)
Background: The aim of this study was to develop a research tool used to assess the efficiency a goalkeeper's actions in a game of futsal.